Respostas

2014-03-05T14:50:15-03:00
7x² - 1 = 5 + 3x
        2          2

mmc (1, 2) = 2
14x² - 1 = 10 + 3x
14x² - 1 - 10 - 3x = 0
14x² - 11 - 3x = 0

a = 14                     b = - 3                           c = - 11
Δ = b² - 4 . a . c
Δ = (- 3)² - 4 . 14 . (- 11)
Δ = 9 + 616
Δ = 625

x = - b ± √Δ
      -------------
         2 . a
x = - (- 3) ± √625
     ------------------------
           2 . 14
x = 3 ± 25
      -----------
         28
x' = 3+ 25 
        28
x' = 28 
÷ 28
x' = 1

x" = 3 - 25 
        28
x" = - 22 ÷ 28
x" = - 11
         14

Resposta: {1; 11/14}
1 5 1